Pengembangan Augmented Reality Sebagai Media dalam Meningkatkan Pemahaman Teks Bacaan - Ali Idrus; Andreo Yudherta (JTP - Jurnal Teknologi Pendidikan, 2016)
The main purpose of unitilize Augmented Reality is to visualize an object virtually in the real world thought visual and verbal(dual-coding). Dual-coding theory, is done to visualize reading text by using augmeted reality. Integration of text and marker on AR, had purposed by four scenarios, as 1) marker was partly made and placed beside text; 2) text directly as a marker; 3) text with frame as a marker; 4) marker as a background of text and made transparently. After the development of application and try outusing AR by using reading text three-demension object could be showed as a marker to trigger the object display.aplication could also track. The text by four diffrent scenerios of marker with the best result is by adding the frame in the text as a marker